2007
DOI: 10.1007/s00445-007-0175-9
|View full text |Cite
|
Sign up to set email alerts
|

A model for radial dike emplacement in composite cones based on observations from Summer Coon volcano, Colorado, USA

Abstract: We mapped the geometry of 13 silicic dikes at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 66 publications
10
46
0
Order By: Relevance
“…Magma conduits may be cylindrical, such as the main vents of Etna, Stromboli and Reunion, or tabular or sheet-like, such as many that feed fissure eruptions in rift zones in the USA, Japan, the Canary Islands and Iceland (e.g., Pollard et al, 1983;Delaney and Gartner, 1997;Gudmundsson, 2002;Acocella and Neri, 2003;Gudmundsson et al, 2008;Keating et al, 2008;Poland et al, 2008;Geshi et al, 2010. The solidification of magma inside these conduits forms plugs and feeder dykes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Magma conduits may be cylindrical, such as the main vents of Etna, Stromboli and Reunion, or tabular or sheet-like, such as many that feed fissure eruptions in rift zones in the USA, Japan, the Canary Islands and Iceland (e.g., Pollard et al, 1983;Delaney and Gartner, 1997;Gudmundsson, 2002;Acocella and Neri, 2003;Gudmundsson et al, 2008;Keating et al, 2008;Poland et al, 2008;Geshi et al, 2010. The solidification of magma inside these conduits forms plugs and feeder dykes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These factors may induce significant deviations from the expected radial pattern of dikes within stratovolcanoes (e.g. Poland et al 2008), explaining the more complex patterns observed in the eroded portions of Etna and Somma-Vesuvius. Fig.…”
Section: Discussionmentioning
confidence: 96%
“…While (a) may explain the radial orientation of the vertically propagating dikes, (b) may indirectly explain the predominance of laterally propagating radial dikes that do not appear to have experienced shallow re-orientation, whose development is commonly expected in stratovolcanoes (e.g. Ode 1957;Poland et al 2008).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The number of radial dikes emanating from magma chambers was counted for this paper along several circular traverses around magma chambers from terrestrial and inferred venusian radial dike complexes. Terrestrial radial dike swarms include Summer Coon Volcano, Colorado (Poland et al, 2008), Mauna Loa, Hawaii (Lockwood and Lipman, 1987), and Dike Mountain, Colorado (Johnson, 1970). Radial structures were counted around the example of the venusian nova given by Head et al (2009).…”
Section: Graben As Surface Expressions Of Dikes At Depthmentioning
confidence: 99%